2007
DOI: 10.1038/sj.bjc.6604133
|View full text |Cite
|
Sign up to set email alerts
|

Antitumour effect of polyoxomolybdates: induction of apoptotic cell death and autophagy in in vitro and in vivo models

Abstract: O. The effect of PM-17 on the growth of cancer cell lines and xenografts was assessed by a cell viability test and analysis of tumour expansion rate. Morphological analysis was carried out by Hoechst staining, flow-cytometric analysis of Annexin V staining, terminal deoxynucleotidyl transferase-mediated 'nick-end' labelling staining, and electron-microscopic analysis. Activation of autophagy was detected by western blotting and fluorescence-microscopic analysis of the localisation of GFP-LC3 in transfected tum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 106 publications
(74 citation statements)
references
References 36 publications
(34 reference statements)
2
71
0
1
Order By: Relevance
“…39,40 Accumulating anticancer agents have been documented to trigger the cellular autophagic process, but the role that autophagy plays in cancer chemotherapy is still controversial. Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…39,40 Accumulating anticancer agents have been documented to trigger the cellular autophagic process, but the role that autophagy plays in cancer chemotherapy is still controversial. Certain anticancer agents i.e., polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagic cell death to enhance chemotherapeutic efficacy, [41][42][43] while others, i.e., suberoylanilide hydroxamic acid, arginine deiminase or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death. [31][32][33] In this study, we demonstrated that quercetin triggered autophagy in human gastric cancer cells both in vitro and in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…Blocking autophagy by utilizing of chloroquine increase the susceptibility to FaDu cell to pro-apoptotic insults (Figure 6), suggesting that delotonin-induced autophagy plays a protective role in FaDu cells. Certain anticancer agents such as polyoxomolybdates-, platonin-or phenethyl isothiocyanate could induce autophagy to enhance chemotherapeutic efficacy [50,51,52], while others, i.e., arginine deiminase, suberoylanilide hydroxamic acid or timosaponin A-III mediated protective autophagy that antagonized apoptotic cell death [53,54,55].…”
Section: Discussionmentioning
confidence: 99%
“…This data suggested deltonin selectivity toward HNSCC cells only. Deltonin showed an IC 50 (median growth inhibitory concentration value) of 3.43 μM after 24 h of treatment, implying that deltonin elicits marked cytotoxic effects on FaDu cells.…”
Section: Cytotoxic Effects Of Deltonin In Cultured Fadu Cell Cellsmentioning
confidence: 99%
“…Two major elements in the Ag 2−x (NH 4 ) x Mo 3 O 10 ·3H 2 O nanowires are expected to have the antibacterial nature, that is, the Ag + ions and the Mo 6+ ions of the composite, both of which have been reported previously [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][41][42][43]. In this work, we have also observed a large amount of Ag-rich nanoparticles on surface of the nanowires.…”
Section: Resultsmentioning
confidence: 99%